Beyond Skills: An Integrative Approach to Doctoral Student Preparation for Diverse Careers - Porter, Susan D.; Phelps, Jennifer M. (Canadian Journal of Higher Education, 2014)
An early consensus in the ongoing discourse about graduate student preparation for diverse careers was that graduates lacked competencies relevant to non-academic professional settings. Lists of missing “skills” were developed that universities and agencies sought to address, most commonly by the offering of generic (transferable) skills workshops or courses. In this paper, we critique this framing of the issue and discuss the limitations of the common approaches taken to address it. We propose a more integrated approach, where students’ thesis research itself is oriented to their possible futures (a practice already occurring in many areas), and where assessment of the competencies so developed is integral to the awarding of the degree. We illustrate the concepts through the stories of two students, and discuss policy ramifications and the substantial challenges to its realization presented by a highly competitive research environment and established ways of assessing success in faculty and students.